1983
DOI: 10.1002/ana.410130612
|View full text |Cite
|
Sign up to set email alerts
|

Passive joint position sense after total hip replacement surgery

Abstract: Passive joint position sense was tested in 10 subjects after unilateral total hip replacement surgery (which included capsulectomy). Varied initial limb position, amplitude, and velocity of movement were used. The unoperated side was used as a control. Statistically barely significant errors (p less than 0.025) on the operated side were detected at 0.6 degrees per second but not at 2 degrees per second. No significant differences were noted among the different hip positions. The results indicate that the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 17 publications
2
21
0
3
Order By: Relevance
“…These results differed from the results of Trudelle-Jackson et al (2002), who only examined patients operated on with the direct-lateral exposure method. This confirmed our assumption that in contrast to sensing the position of the joint (Grigg et al, 1973;Karanjia and Ferguson, 1983), the condition of the joint capsule considerably influenced the balancing ability. In the case of postero-lateral exposure, Nallegowda et al (2003) found that 8 months after THA, the results of stabilometry testing conducted with the eyes open did not differ significantly from the control group, even when the tests were performed on a plate with sinusoidal motion.…”
Section: Type Of Testsupporting
confidence: 86%
See 1 more Smart Citation
“…These results differed from the results of Trudelle-Jackson et al (2002), who only examined patients operated on with the direct-lateral exposure method. This confirmed our assumption that in contrast to sensing the position of the joint (Grigg et al, 1973;Karanjia and Ferguson, 1983), the condition of the joint capsule considerably influenced the balancing ability. In the case of postero-lateral exposure, Nallegowda et al (2003) found that 8 months after THA, the results of stabilometry testing conducted with the eyes open did not differ significantly from the control group, even when the tests were performed on a plate with sinusoidal motion.…”
Section: Type Of Testsupporting
confidence: 86%
“…It has been shown in earlier research that at half a year and 1 year after THA, the perception of the joint position corresponds to that of healthy subjects (Grigg et al, 1973;Karanjia and Ferguson, 1983). A presumable reason for this is that the state of the hip joint surface and of the joint capsule has a much smaller impact on the perception of the joint position (Grigg et al, 1973) than the state of the articular ligaments and periarticular muscles (Ishii et al, 1999).…”
Section: Introductionmentioning
confidence: 92%
“…Other studies comparing joint position sense between subjects' uninvolved hip and their surgically replaced hip have concluded that joint position sense remains intact after THA. 8,11 Residual muscle strength deficits may contribute to impairment in postural stability. In the current study, strength deficits that ranged from 2.2% for the knee flexors to 18.0% for the hip flexors were not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…54 Controversy exist over the relative contribution to proprioception of muscle receptors versus joint receptors. 57,59,66 Both receptor types probably function as complementary components of the afferent system. It can also be noted that rotations into the limit of joint motion result in progressively smaller length changes in the muscles and in progressively larger tension in the joint capsule.…”
Section: 48mentioning
confidence: 99%